Key principles for assessing and implementing remote inspection with telexistence capability - Mazeas, Damien Jean Maxime (Cranfield University, 2023)
This thesis investigates assessing and implementing telexistence capabilities for enhancing remote inspection and control in hazardous environments. Telexistence, allowing virtual presence via robotic systems or avatars, is crucial for performing high-risk tasks in fields like marine engineering. The research integrates virtual reality, industrial robotics, and sensors to improve human abilities in maintenance, repair, and overhaul tasks, aiming for safer and more efficient methods in hazardous settings. A key aspect is the design and evaluation of telexistence interfaces for remote visual inspection, focusing on interfaces that enhance operators' sense of presence and spatial awareness, crucial for decision-making in risky conditions. A proposed system architecture is validated with a real-world use case and used as a basis for two user studies. The first study compares the effectiveness of a 2D and a VR interface in remote visual inspection in machinery spaces, leading to recommendations for enhancing telexistence in maintenance scenarios. The second study examined the impact of interface design on operators’ telexistence capabilities at a cognitive workload level, using modalities like 2D feeds, 3D point clouds, augmented virtuality, and mixed modalities. A central theme is using VR to bridge the gap between human operators and robots. VR's immersive nature improves operators' remote-control abilities, with a digital representation in a VR control room mirroring the robot's actions in real- time, enhancing remote-control effectiveness and providing a more immersive telexistence experience. Key findings demonstrate the advantages of immersive VR interfaces over traditional 2D interfaces in remote visual inspection tasks. VR interfaces offer a heightened sense of presence, reduced cognitive workload, and improved usability, leading to more efficient and accurate task execution. Additionally, VR users experienced fewer errors and completed tasks faster. Different visualisation modalities also showed varied impacts on cognitive load, with 3D modality imposing the most substantial demands.
Noel, Frederic - Associate Supervisor (Grenoble University)
Keywords: Telexistence; Virtual Reality; Remote Inspection; Remote Control; Human Factors; Human-Computer Interaction